2007
DOI: 10.1186/gb-2007-8-12-r259
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of phycobilisomes in marine Synechococcusspp.: a comparative genomics study

Abstract: Phycobilisome diversity and evolution

By comparing Synechococcus genomes, candidate genes required for the production of phycobiliproteins, which are part of the lightharvesting antenna complexes called phycobilisomes, were identified. Phylogenetic analyses suggest that the phycobilisome core evolved together with the core genome, whereas rods evolved independently.

Abstract Background: Marine Synechococcus owe their specific vivid color (ranging from blue-green to orange) to their large extrinsic ante…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
432
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(452 citation statements)
references
References 75 publications
17
432
2
1
Order By: Relevance
“…This can be explained in three ways, by extensive homoplasy (backward and/or parallel mutations), horizontal gene transfer of the cpcBA operon or by a lack of data. These results are in line with recent genome analysis of several marine Synechococcus strains, which indicated that genes encoding PC and PE I and II show different evolutionary relationships in comparison with genes of the core genome such as the allo-PC gene or the ribosomal regions (Six et al, 2007). Finally, neighbour-net analysis of the cpcBA phylogeny indicated that the PE-rich isolates of the BSea group are only distantly related to other known Synechococcus isolates ( Figure 5).…”
Section: Microdiversity Recombination and Endemismsupporting
confidence: 74%
See 4 more Smart Citations
“…This can be explained in three ways, by extensive homoplasy (backward and/or parallel mutations), horizontal gene transfer of the cpcBA operon or by a lack of data. These results are in line with recent genome analysis of several marine Synechococcus strains, which indicated that genes encoding PC and PE I and II show different evolutionary relationships in comparison with genes of the core genome such as the allo-PC gene or the ribosomal regions (Six et al, 2007). Finally, neighbour-net analysis of the cpcBA phylogeny indicated that the PE-rich isolates of the BSea group are only distantly related to other known Synechococcus isolates ( Figure 5).…”
Section: Microdiversity Recombination and Endemismsupporting
confidence: 74%
“…The PE-rich strains could not be differentiated from the PC-rich strains on the basis of their 16S rRNA-ITS sequences. However, this clearly visible phenotypic differentiation was genetically supported by the cpcBA operon, which separated many of the PE-rich strains from the PC-rich strains (Figure 3; see also Six et al, 2007;Haverkamp et al, 2008). Other phenotypic differences, in cell size and cell volume, did not match the separation into different phylogenetic clusters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations